Artificial intelligence and pharmacy education: a survey to assess the knowledge, application, and perspective of B. Pharm. students from India - V. U Risana; Asheekha Shirin; Rukhiya Naduvile Purayil; Sandra Rose Mathew; Sauparnika Soman; C. Sarath Chandran; S. S. Kiron (Discover Education)
Abstract This study aimed to understand the knowledge, application, and perspective of B. Pharm students regarding artificial intelligence (AI) tools. This study used a quantitative cross-sectional observational design, and data were collected using a questionnaire. The questionnaire was distributed among B. Pharm students in India, and 305 participants were included in the study. The results of the study showed that the majority of participants were female, and the mean age of the participants was 20.51 years. The study also found that the participants had limited knowledge of AI and its applications in pharmacy education. Only 34.6% of participants attempted to integrate AI tools into their academic activities. The most commonly used integrated tools were ChatGPT (42.2%) and Google Bard (Gemini) (30.8%). The survey strongly indicated the inclination of the pharmacy student community towards generative AI tools for academic purposes. However, the participants showed positive attitudes towards the use of AI in pharmacy education and believed that it would improve the quality of their education. A significant majority (82.3%) of respondents express interest in attending workshops or training sessions to enhance their knowledge about AI, The study concluded that there is a need for educators and technology creators to develop strategies to integrate AI into pharmacy education to improve the learning experience of students.